The Implementation of Jelajah Alam Sekitar-based Worksheets on Environmental Pollution Material - Kusumawati, Endah; Ngabekti, Sri; Budi Prasetyo, Andreas Priyono (FMIPA UNNES, 2019)
Implementation of Jelajah Alam Sekitar-based worksheets (JAS) aims to improve student learning outcomes at SMPN 38 Semarang. JAS-based worksheets were developed by utilizing the environment around the school. Environmental problems are presented based on observations of environmental conditions around the school. Environmental problems around the school are presented in practical activities to increase student participation in learning. Experimental class learning using JAS-based worksheets with sources of environmental problems. The control class uses worksheets created by the teacher, learning with a cooperative model with a discussion method. This research uses a Quasi experimental design method with a Non-equivalent Control Group Design design. The population of this research is all students of class VII SMPN 38 Semarang. The research sample was determined by a purposive sampling technique, namely class VII D and class VII A. The results showed that the learning outcomes of the experimental class students were better than the control class in terms of cognitive, psychomotor and affective aspects (discipline and cooperation attitude). The results of the cognitive and psychomotor aspects t-test results were respectively obtained tcount (0.05) = 4.63 and tcount (0.05) = 4.18 with ttable = 2.001 then tcount> ttable, meaning that there were significant differences in results cognitive and psychomotor learning of students between the experimental class with the control class. Results of student’ environmental care attitude in this research were not significant.